DESIGN EXPLORATION OF LOCAL BAMBOO MATERIALS FOR AN ECO-FRIENDLY PHOTO SPOT BRIDGE IN KAMPOENG BOENGA GRANGSIL - Triska Prakasa Wikananda; Respati Wikantiyoso; Dina Poerwaningsih; Sari Mawaddahni (Architecture Study Program, Faculty Of Engineering, University of Merdeka Malang, 2025)
Kampoeng Boenga Grangsil (KBG) is a developing rural tourism destination located in Malang Regency, East Java Province, with its main attractions rooted in the natural landscape and community-based floriculture. The transformation of the KBG tourist destination has been conceptualized as a Master Plan for advancing KBG from 2020 to 2030. The KBG Development Masterplan for 2020-2030 constitutes a Long-Term Development Strategy (10 Years) for KBG, delineated into two distinct phases of development. As tourism activities grow, the demand for attractive and environmentally responsible support facilities becomes more urgent. One of the key challenges is the absence of iconic photo spots that can enhance the site's visual identity and visitor experience. This study aims to design a photo spot bridge using local bamboo material, integrating environmentally friendly architectural principles and a participatory approach involving local stakeholders. The research and design process adopted a community-based participatory method facilitated by a Community Service Program (Partner Village Development) team. The process involved collaborative ideation, material exploration, and co-construction with residents. Bamboo was selected as the primary material due to its local abundance, sustainable characteristics, and cultural relevance within the community. The design outcome is a bamboo photo spot bridge prototype that aligns with the site's natural aesthetics, supporting environmental sustainability and strengthening the destination's visual identity. Community participation throughout the planning and construction phases contributed to a strong sense of ownership and local capacity-building. The study recommends adopting similar participatory and material-conscious approaches for future facility development within Kampoeng Boenga Grangsil and other rural tourism destinations. It also highlights the importance of incorporating eco-education elements and sustainable construction techniques in long-term tourism development strategies